The Playing Session: Enhanced Playability for Mobile Gamers in Massive Metaverses. (23rd June 2008) - Cacciaguerra, S.; D'Angelo, G.
Abstract : Internet ubiquity and the success of mobile gaming devices are increasing the interest in wireless access to virtual environments. Mainly due to the mobility factor and wireless medium features, traditional gaming architectures are not enough to guarantee good levels of playability and fairness to mobile gamers. We suggest a new mechanism, called playing session, capable of controlling communications between mobile devices and the game infrastructure. In case of network failures, a mimicking mechanism is in charge of playing, until the communication channel is restored. The goal is to reproduce, with an adequate level of mimesis, the user behavior. According to this approach, it will be possible to enhance the overall playability of Internet games without requiring any modification to the existing communication infrastructure.